European Union Open Data Portal: analysis and evaluation - Arquero Avilés, Rosario; Marco Cuenca, Gonzalo (Revista General de Información y Documentación, 2014)
The open data movement (Open Government Data) is linked to the principles of transparency, participation and collaboration. In line with these principles, the policies of opening and release of data from governments connect with the aspect of the provision of organizations, companies and citizens to public sector information that can be reused and add value. In this context is presented an analysis of the open data portal of the European Union as a data source and a single point of access to the data produced by other institutions and bodies of the European Union. The aim of the work is focused on addressing the study of its contents, standards on which it is based, as well as major datasets, formats and applications available.